Application of Laminated Veneer Lumber (LVL) on the Wooden Boat Construction - Ahmad Basuki Widodo (IPTEK The Journal for Technology and Science, 2012)
LVL (Laminated-Veneer Lumber) has many advantages and economic values, which is important for wooden boat construction. The recovery of veneer, the main material of LVL, are higher than sawn-timber and their drying process are faster. LVL produced with a continuous press has been approved as an engineered material with reliable strength and stiffness. In a wooden boat processing, the easy forming into a curve shape and strength are main factor, because of the streamline shape of boats. LVL material is able to meet those requirements. As an endless-length LVL is made from a log limited-length hence LVL always contain joints. Butt joint have numerous drawbacks, but they are inherently simple and less time to manufacture than other joints types. The purposes of this experiment are to investigate the basic characteristics of LVL which are important for deck and hull planking in the wooden boat constructions. Yellow meranti and red meranti were peeled by a veneer lathe and phenol formaldehyde adhesive were used. Result of experiment indicated that at the position 0o (β), the flexibility and strength of LVL up to proportional limit increased with increasing number of layer and spacing of butt-joint (d/t). LVL at the position 45o and 90o (β), all types of LVL had lower flexibility and strength than the standard value for deck and hull planking. In bending experiment test speciment at position 45° with direction of grain, maximum width of LVL equal to the spacing of frame and at position 90° equal to the width of hull planking in wooden boat. Based on the interpretations of the above results, it can be concluded that (1). LVL of 9, 6 and 4 plies with upside (inside) veneer butt-joint is appropriate for deck and hull planking in wooden boat manufacturing, (2). LVL of 9, 6 and 4 plies with spacing of butt-joint (d/t) more than 20 is appropriate for deck and hull planking in manufacturing wooden boat.